The Sociology of Cartels - Justus Haucap; Christina Heldman (Center for Economic Studies and ifo Institute (CESifo), 2022)
Traditional economic theory of collusion assumed that cartels are inherently unstable, and yet some manage to operate for years or even decades. While the literature has presented several determinants of cartel stability, the vast majority focuses on firms as entities, even though cartels are typically formed between individuals who need to develop structures that allow them to establish trust and ensure cooperation. We analyze 15 German cartels, focusing on the individual participants, the communication and internal structures within the cartels as well as their breakup. Our results indicate that cartel members are highly homogeneous and often rely on existing networks within the industry. Most impressively, only two of the 156 individuals involved in these 15 cartels were female, suggesting that gender also plays a role for cartel formation. We further identify various forms of communication and divisions of responsibilities and show that leniency programs are a powerful tool in breaking up cartels. Based on these results we discuss implications for competition policy and further research.
Keywords: L41; K21; Z13; 330; cartels; collusion; social networks; trust; antitrust